EXISTENCE OF THE ISOLATED SPECIAL POINTS THREE-DIMENSIONAL DIFFERENTIAL SYSTEMS OF A SPECIAL LOOK (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In article the research of a system of the differential equations for a three-dimensional case on distribution of the isolated special points when the right side consists composed from a constant square matrix and a scalar form of degree is considered k ? 1. Here it is supposed that own matrixes valid and various, and are not equal to zero. Linear transformation where the square matrix of transformation is nondegenerate is entered. In a required system the educated new matrix of coefficients has simpler appearance and this matrix can give a type of a Jordan normal form. Further, passing to scalar record of a system, its canonical form is received.